Image Quality of Digital Direct Flat-Panel Mammography Versus an Indirect Small-Field CCD Technique Using a High-Contrast Phantom - Kathrin Barbara Krug; Hartmut Stützer; Peter Frommolt; Julia Boecker; Henning Bovenschulte; Volker Sendler; Klaus Lackner (International Journal of Breast Cancer)
Objective. To compare the detection of microcalcifications on mammograms of an anthropomorphic breast phantom acquired by a direct digital flat-panel detector mammography system (FPM) versus a stereotactic breast biopsy system utilizing CCD (charge-coupled device) technology with either a 1024 or 512 acquisition matrix (1024 CCD and 512 CCD). Materials and Methods. Randomly distributed silica beads (diameter 100–1400 𝜇m) and anthropomorphic scatter bodies were applied to 48 transparent films. The test specimens were radiographed on a direct digital FPM and by the indirect 1024 CCD and 512 CCD techniques. Four radiologists rated the monitor-displayed images independently of each other in random order. Results. The rate of correct positive readings for the “number of detectable microcalcifications” for silica beads of 100–199 𝜇m in diameter was 54.2%, 50.0% and 45.8% by FPM, 1024 CCD and 512 CCD, respectively. The inter-rater variability was most pronounced for silica beads of 100–199 𝜇m in diameter. The greatest agreement with the gold standard was observed for beads >400 𝜇m in diameter across all methods. Conclusion. Stereotactic spot images taken by 1024 matrix CCD technique are diagnostically equivalent to direct digital flat-panel mammograms for visualizing simulated microcalcifications >400 𝜇m in diameter.